Juvenile massive fibroadenoma - El Ters, Escandor; Lista, Ricardo; Miranda, Elber; Perrone, Luis (Cirugía del Uruguay, 1995)
The authors present a new case of juvenile massive fibroadenoma involving almos/ al/ the breas/ in a 14 year old patient. They analise diagnostic difficulties and surgical treatment adopted in this case: ubcutaneous mastectomy and breas/ reconstruction with silicon prothesis and its aesthetic result.